Lactational Failure in Sahiwal Friesian Cows - Marimuthu, Murugaiyah (2000)
Sahiwa1 Friesian cows have been bred specifica1ly for dairying in Malaysia for the past 20 years but there still exist a proportion of these cows having a lactation period less than 60 days of milk production. The aim of this project was to determine the physiologica1 incidence and characteristics of lactation persistency and to identify factors that might be responsible for cessation of milk secretion in lactational failure cows (LF). The study on the milking characteristics exhibited a high residua1 milk volume in early lactation, which increased with stage of lactation in the LF cows. Milk storage studies in the udder indicated there was no significant difference in the characteristics of milk distribution between a1veolar lumina and gland cistern with time after milking between the norma1 and LF cows. This indicated that retention of residual milking after milking was more likely to be a consequence of a defective neuroendocrine letdown reflex, perhaps involving insufficient systemic oxytocin or mammary insensitivity to oxytocin. Analysis of the metabolic activity of the mammary epithelial (milk secreting) cells and estimation of mammary cell numbers suggested that the lactational failure in the Sahiwal Friesian cows was due, at a cellular level, to loss of a proportion of the secretory epithelial cell population. This finding indicates premature involution of the mammary gland in the LF cows. Prolactin measurements during the early lactation showed that there was no evidence of differences between normal and LF cows. It was only after the fourth week onwards of lactation, that there was a steady decrease in prolactin levels in the lactational failure cows. Therefore, it appears unlikely that an inherent deficiency in prolactin secretion in LF cows, apparent from the first weeks post partum, had compromised mammary development and so precipitated lactational failure. In conclusion, the results obtained in this project suggest that a principal cause of lactation failure in Sahiwal Friesian cows is a progressive increase in the proportion of milk left in the gland after milking. Oxytocin treatment may alleviate the problem if residual milk is primarily a consequence of restricted oxytocin release at milking. The roles of other galactopoietic hormones remain to be established.